2005
DOI: 10.3310/hta9160
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial to compare the cost-effectiveness of tricyclic antidepressants, selective serotonin reuptake inhibitors and lofepramine

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 82 publications
4
53
0
2
Order By: Relevance
“…In line with recommendations from a HTA-funded primary care depression trial by Peveler and colleagues, 16 GP practices were reimbursed for the additional time involved in recruitment of patients to the trial via service support costs. An additional GP practice incentive was the use of the Quality and Outcomes Framework (QOF).…”
Section: Recruitment Into the Trialmentioning
confidence: 98%
See 1 more Smart Citation
“…In line with recommendations from a HTA-funded primary care depression trial by Peveler and colleagues, 16 GP practices were reimbursed for the additional time involved in recruitment of patients to the trial via service support costs. An additional GP practice incentive was the use of the Quality and Outcomes Framework (QOF).…”
Section: Recruitment Into the Trialmentioning
confidence: 98%
“…We therefore powered our trial both to capture any benefit of cCBT over usual GP care alone and to test the non-inferiority of free-to-use cCBT. We based our sample size calculation on the usual care arm of our own primary care trial of collaborative care for depression, where the proportion of patients responding to usual care was in the region of 0.6; 29 a response rate similar to that found in a UK HTA trial of antidepressants in primary care 16 and a US pragmatic depression trial. 30 We regarded a response rate of not more than 0.15 below this rate as being acceptable, given the additional care options that are available to patients who do not initially respond to cCBT within a stepped care framework.…”
Section: Sample Sizementioning
confidence: 99%
“…Six studies 139,142,144,[147][148][149] investigated the known-group validity of the EQ-5D across severity groups, five studies 129,136,137,143,145 reported convergent validity of the EQ-5D and 14 studies 50,[130][131][132][133][134][135][136][137][138]140,141,145,146 investigated the responsiveness of the EQ-5D. Two studies 139,142 had known-groups differences in the SF-6D, three 132,134,137 had convergent validity and two 136,145 had responsiveness.…”
Section: Depression and Anxietymentioning
confidence: 99%
“…In all, there were 22 studies 50, identified with data on the validity and/or responsiveness of the generic HRQoL measures in depression and anxiety for EQ-5D and SF-6D. Fourteen studies 50,129,[136][137][138][139][142][143][144][145][146][147][148][149] had data on the EQ-5D and seven 130,131,[133][134][135]140,141 contained data on the SF-6D. Studies were undertaken in at least 12 countries (a number covered Europe).…”
Section: Depression and Anxietymentioning
confidence: 99%
“…An open, pragmatic randomised trial by Peveler et al (2005) compared three treatments for depression in primary care: a tricyclic antidepressant (TCA, choosing one of three options), a selective serotonin reuptake inhibitor (SSRI, choosing again one of three options) and lofepramine. Among the outcome indicators used was the EQ-5D, alongside more familiar depression scales.…”
Section: Using Qalys In Mental Health Researchmentioning
confidence: 99%